ETHICAL USE OF DATA AND ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN ORGANIZATIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article analyzes the importance of ethical principles in the use of data and artificial intelligence technologies in organizations, their impact on management processes, and issues of security, transparency, and responsibility based on a comprehensive scientific approach. In the process of digital transformation, the widespread use of large-scale data collection and automated decision-making systems creates new opportunities, as well as ethical problems. The study examined the issues of data privacy, algorithmic justice, prevention of discrimination, protection of human rights, and accountability of artificial intelligence systems. Ethical standards and corporate governance practices developed by international organizations were analyzed, and scientific conclusions were drawn on the formation of responsible AI policies in organizations. The results of the study show that the systematic implementation of ethical principles increases the effectiveness of the use of artificial intelligence and strengthens trust in organizations.